Epidemiology of Lyme Disease - Dennis J White (Canadian Journal of Infectious Diseases)
Investigation of the epidemiology of Lyme disease depends upon information generated from several sources. Human disease surveillance can be conducted by both passive and active means involving physicians, public health agencies and laboratories. Passive and active tick surveillance programs can document the extent of tick-borne activity, identify the geographic range of potential vector species, and determine the relative risk of exposure to Lyme disease in specific areas. Standardized laboratory services can play an important role in providing data. Epidemiologists can gain a better understanding of Lyme disease through the collection of data from such programs. The interpretation of data and provision of information to the medical and general communities are important functions of public health agencies.